2001
DOI: 10.1037/0022-0663.93.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive constraints on multimedia learning: When presenting more material results in less understanding.

Abstract: In 4 experiments, college students viewed an animation and listened to concurrent narration explaining the formation of lightning. When students also received concurrent on-screen text that summarized (Experiment 1) or duplicated (Experiment 2) the narration, they performed worse on tests of retention and transfer than did students who received no on-screen text. This redundancy effect is consistent with a dual-channel theory of multimedia learning in which adding on-screen text can overload the visual informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
514
10
21

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(564 citation statements)
references
References 30 publications
19
514
10
21
Order By: Relevance
“…Because text is initially processed in the visual subsystem of working memory, it competes with the graphic for visual attention. Although the words may eventually be translated into sounds in verbal working memory, this initial competition decreases the likelihood that the learner will attend to the relevant elements of the graphic and text (Mayer, Heiser, & Lonn, 2001). Typically when auditory information is presented in the verbal subsystem, the load on working memory is reduced (due to an increase in working memory capacity) allowing more resources to be devoted to learning.…”
Section: Modality Effectmentioning
confidence: 99%
“…Because text is initially processed in the visual subsystem of working memory, it competes with the graphic for visual attention. Although the words may eventually be translated into sounds in verbal working memory, this initial competition decreases the likelihood that the learner will attend to the relevant elements of the graphic and text (Mayer, Heiser, & Lonn, 2001). Typically when auditory information is presented in the verbal subsystem, the load on working memory is reduced (due to an increase in working memory capacity) allowing more resources to be devoted to learning.…”
Section: Modality Effectmentioning
confidence: 99%
“…A diagram and text that redescribes the diagram provides an obvious example as does presenting the same material in written and spoken form. The redundancy effect is demonstrated when eliminating the redundant material improves learning (see Cerpa, Chandler and Sweller 1996;Sweller 1991, 1996;Craig, Gholson and Driscoll 2002;Kalyuga, Chandler and Sweller 1999;Mayer, Heiser and Lonn 2001;Mayer, Bove, Bryman, Mars and Tapangco 1996;Anderson 1980, 1982;Sweller and Chandler 1994).…”
Section: Cognitive Load Theorymentioning
confidence: 99%
“…Irkin (2012) emphasized that cartoons with content of violence and sexuality make students develop negative behaviors. Mayer et al (2001) stated that cartoons have a potential of misconception since they are a simplified version of a phenomenon in most cases and may prevent students from learning through imagination while forming their mental models. Ningsih and Sari (2012) suggested that use of slang and foreign words may affect children's linguistic development negatively, that watching cartoons excessively may hinder children's relationship with the social circle and cause them to lose their critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%